2009
DOI: 10.4172/plastic-surgery.1000594
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic cutaneous breast carcinoma: A case report and review of the literature

Abstract: Cutaneous metastatic carcinoma, also known as carcinoma erysipeloides, is an unusual clinical finding. In women, it is most frequently found in association with breast cancer rather than other visceral malignancies. Breast cancer patients can present with cutaneous manifestations of breast disease at the time of their initial diagnosis; however, cutaneous metastases more often present well after the initial diagnosis and treatment of the breast disease. Prompt recognition of skin metastases by the plastic surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 10 publications
1
18
0
2
Order By: Relevance
“…Furthermore, in our study, breast metastases were frequently found on the anterior chest, a common place for this malignancy, as cited in the literature 2,17 , but also on the head and limbs. Lung carcinomas preferred the thorax and also the head and neck, whereas the digestive tract and ovary predilection for the abdomen was once again confirmed 14 .…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, in our study, breast metastases were frequently found on the anterior chest, a common place for this malignancy, as cited in the literature 2,17 , but also on the head and limbs. Lung carcinomas preferred the thorax and also the head and neck, whereas the digestive tract and ovary predilection for the abdomen was once again confirmed 14 .…”
Section: Discussionsupporting
confidence: 81%
“…In alcuni casi si può avere anche una diffusione cutanea, sia locoregionale (cioè vicino alla sede dell'intervento di asportazione) sia a distanza (in una zona di cute non vicina alla mammella trattata chirurgicamente). Nava e Greer [9], riferendosi ai carcinomi mammari, riportano un'incidenza di metastasi cuta nee fino al 24%. In questi casi non bisogna sottovalutare assolutamente la situazione: le metastasi cutanee possono essere infatti il primo riscontro clinico di metastatizzazione diffusa oltre la cute [10].…”
Section: Le Metastasi Cutaneeunclassified
“…The clinical manifestation of carcinoma erysipeloides indistinguishably resembles erysipelas or cellulitis. However, its specific clinical features such as lack of systemic fever, absence of circulating leukocytosis, and resistance to antibiotics would help to distinguish it from acute infectious diseases 7 . We could not suspect metastatic skin carcinoma at the first visit as the symptoms and laboratory data (elevated C‐reactive protein and leukocytosis) were compatible with those of cellulitis.…”
mentioning
confidence: 94%